Pemanfaatan Musik Etnik Dayak Ma’anyan Dalam Pelayanan Musik Gereja Di Jemaat GKE Eben Ezer - Pransinartha; Salmanezer, Jonathan; Wowiling, Meiske Lydia Paulina (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2025)
The Evangelical Christian Church of Kalimantan (GKE) Eben Ezer Banjarmasin is one of the churches striving to utilize its musical potential to support its ministry. One form of music that has been highlighted is the ethnic Dayak Ma’anyan music, which is rich in cultural values and local wisdom. The problem identified in this study is the suboptimal utilization of ethnic Dayak Ma’anyan music in church music ministry. The research method employed is qualitative descriptive, with data collection techniques including observation, interviews, and documentation. The findings are as follows: (1) The utilization of ethnic Dayak Ma’anyan music at GKE Eben Ezer plays a role in cultural preservation and inspires congregational hymns; (2) The application of Peter Shineller's inculturation theory in the development of church music enriches the understanding of the inculturation process of Dayak Ma’anyan ethnic music; (3) The use of Graham Wallas' creative thinking theory facilitates the creation of new, systematic, and innovative music; (4) The newly created inculturated Dayak Ma’anyan music received positive responses from the congregation; and (5) The formation of a new music group at GKE Eben Ezer, based on Dayak Ma’anyan ethnic music, demonstrates significant progress in the church’s music ministry at GKE Eben Ezer Banjarmasin.